Empirical equations for calculating the rate of liquid flow through GCL-geomembrane composite liners. Issue 2 (April 2006) - Touze-Foltz, N.; Barroso, M.
Abstract : This paper presents equations for the evaluation of advective flow rates though composite liners involving GCLs. Advective flow is due to the existence of defects in the geomembrane, and depends on the contact condition between the geomembrane and the GCL. In this paper the geomembrane-geosynthetic clay liner contact condition is quantitatively defined, based on experimental data. Accordingly, empirical equations are presented for circular defects having diameters in two different ranges: 2 to 20 mm and 100 to 600 mm. The validity of the empirical equation obtained for the smallest range of diameters is compared with experimental results and with an existing empirical equation. The empirical equations developed in this paper are then combined in a simple analytical solution, leading to semi-empirical equations that allow one to predict flow rates for narrow and wide defects, taking account of the flow that takes place at both ends of these defects of finite length. A parametric study shows, through a correlation factor, the importance of the flow at both ends of defects of finite length, mainly for narrow defects.